Remembering Ludlow but forgetting the Columbine : the 1927-1928 Colorado Coal Strike - Campbell-Hale, Leigh (Mining the American West., 2023)
"This work examines the causes, context, and legacies of the Columbine Massacre in relation to the history of labor organizing, giving attention to a forgotten event remembered now as the Columbine Massacre, in which police shot and killed six striking coal miners and wounded sixty more protestors during the Colorado Coal Strike"--